Quality of Caregiver–child Interactions in Early Child Care Centers in Bangladesh: Measurement and Training. Issue 1 (2nd January 2023) - Helmerhorst, K. O. W.; Dutta, M.; Khanom, F.; Zaman, S. S.; Gevers Deynoot-Schaub, M. J. J. M.
ABSTRACT: The current study assessed (1) the importance of six caregiver interactions skills (sensitive responsiveness, respect for autonomy, structuring and limit setting, verbal communication, developmental stimulation, and fostering positive peer interactions) as rated by several stakeholders, (2) the quality of caregiver interactive skills, and (3) the effectiveness of a training program in early child care centers (children 0- to 6-year-olds) in Bangladesh. Using a quasi-experimental study design, 20 caregivers were allocated to the experimental condition (receiving a training) and 20 caregivers to the control condition (no training). Research Findings : Results showed that the importance of the six caregiver interactive skills was acknowledged by parents, managers/factory owners, and caregivers. Caregivers scored on average in the inadequate range for five out of the six CIP skills (except structuring and limit setting). Using a newly developed training program, quality of caregiver interactive skills improved. Finally, caregivers' overall training satisfaction as rated at posttest was high. The relatively low scores on caregiver interactive skills underscore that it is important to assess and monitor pedagogical quality in child care. Practice or Policy : Our findings indicate that the quality of caregiver–child interactions in the Bangladesh child care context can be strengthened by training.